A Study on Chaos-Based System for Improved Encryption of Images (International Journal of Engineering and Computer Science, 2015)
In modern world, encryption technology has been developed rapidly the chaos based cryptographic algorithms. Chaos based cryptographic recommend a variety of features over the traditional encryption algorithms such as high security, speed, and prudent computational overheads and power. Chaos theory studies the performance of dynamical systems that are enormously sensitive to initial conditions, which means that a small change in the initial state can be lead to a big diverse action in the final state. This paper presents a study on chaos based system for improved encryption of images using RSA public key cryptography.